The protective effect of alfalfa (Medicago sativa L.) seed extract containing polysaccharides on human keratinocytes and fibroblasts - Kim, Jeeyoung; Bang, Weon Jeong; Woo, Jung; Kim, Younghwa; Shin, Hee Jung; Kim, Junoh; Kim, Min-Gi; Joo, Yung Hyup; Lee, Chang-Seok (Archives of Biological Sciences, 2023)
Paper description: The skin protective effect of alfalfa seed extract containing polysaccharides (APE) has not been well studied. The expression of epidermal proteins was assessed to monitor differentiation and skin barrier function in APE-treated keratinocytes, and the anti-inflammatory and anti-aging effects of APE on dermal fibroblasts. APE upregulated the genes encoding filaggrin, involucrin and claudin1, but inhibited elastase activity, matrix metalloproteinase-1 secretion and interleukin (IL)-6 and IL-8 production. We show the protective effect of APE on human skin cells for the first time, which suggests that APE may be a potent beneficial component for promoting skin health in cosmetic and medicinal applications. Abstract: To protect the body against environmental threats, cosmetics can play important antiinflammatory and anti-aging roles. Many researchers have developed cosmetic ingredients using natural plant extracts or the active compounds of such extracts. In this study, we assessed the ability of extracts from the seeds of alfalfa (Medicago sativa L.) to affect skin cells. In a keratinocyte-derived cell line (HaCaT cells), alfalfa polysaccharide extract (APE) treatment triggered cornified envelope formation and increased the gene expression levels of filaggrin and involucrin, suggesting that APE increased epidermal cell differentiation. In addition, APE dramatically increased the mRNA and protein levels of claudin1, suggesting that it enhances tight junction formation. Finally, APE exerted antiinflammatory effects in keratinocytes by decreasing the LPS-induced production of proinflammatory cytokines. In primary normal human dermal fibroblasts (NHDF), APE increased procollagen synthesis and decreased elastase activity and metalloproteinase-1 (MMP) secretion. APE also showed superoxide dismutase (SOD)-like activity in a cell-free system, resulting in antioxidant effects. Finally, we found that the polysaccharides from alfalfa seeds used in our experiments consist mainly of galactose and mannose. Based on our findings, we conclude that APE may have potent skin-protective and skin-improving effects and could be developed as an important ingredient in cosmetics and medicines.